Hand grip strength determination for healthy males in Saudi Arabia: A study of the relationship with age, body mass index, hand length and forearm circumference using a hand-held dynamometer. (April 2017) - Alahmari, Khalid A; Silvian, S. Paul; Reddy, Ravi Shankar; Kakaraparthi, Venkata Nagaraj; Ahmad, Irshad; Alam, Mohammad Mahtab
Objectives: To determine whether age, body mass index (BMI), hand length and forearm circumference were predictive of hand grip strength in healthy Saudi Arabian adult males. Methods: This cross-sectional descriptive study recruited healthy adult male volunteers. Their anthropometric characteristics including age, BMI, hand length and forearm circumference were measured using routine techniques. Hand grip strength was assessed using a Jamar® Hydraulic Hand Dynamometer. The data were analysed using Pearson correlation coefficient ( r ) as well as by a stepwise multiple linear regression analysis. Results: The study included 116 healthy males who satisfied the inclusion criteria. A Pearson correlation coefficient matrix demonstrated that all the four measures, age, BMI, hand length and forearm circumference, were significantly correlated with hand grip strength. Age had an inverse correlation with hand grip strength. The anthropometric measures of hand length, age and forearm circumference accounted for 44.2% (R 2 0.442) of the variation of the hand grip strength. Conclusion: Hand length, age and forearm circumference significantly impacted on hand grip strength in Saudi Arabian healthy adult males.